Purification and immunochemical characterization of Streptococcus sanguis serotype I carbohydrate antigen. - Okahashi, N (1983)
The serotype-specific antigen of Streptococcus sanguis ST3 (serotype I, biotype A) was extracted, chromatographically purified, and characterized by immunological and chemical methods. The antigen was extracted from purified cell walls with hot trichloroacetic acid, followed by ion-exchange chromatography on a DEAE-Sephadex A-25 column and gel filtration through a Sephadex G-100 column. A peak fraction was obtained that gave a single precipitin band when reacted with anti-type I serum. The type I antigen was a polysaccharide composed of glucose, rhamnose, and N-acetylglucosamine in a molar ratio of 1.4:2.5:1.0. Quantitative precipitin inhibition tests with various haptenic sugars indicated that an alpha-glucosidic linkage is the immunodeterminant of the type I antigen.